Features of financial analysis in the environmental organization LLC «LEMVA» - E. A. Kirova; A. A. Kurchenko (Вестник университета)
This article is devoted to the peculiarities of financial analysis in an environmental organization. For effective financial analysis of a particular enterprise, it is relevant and necessary to assess the specifics of its activities, which affects the specifics of financial analysis. The purpose of the research in the article is to develop a methodology for financial analysis of an environmental enterprise, taking into account the specifics of its activities, for which both general scientific and private indicators of such an assessment were used. The tasks solved in the article include: determining the factors that define the features of the financial analysis of an enterprise in the environmental sector, developing and testing the author’s algorithm for the financial analysis of the enterprise, identifying the problems of the financial situation of the company and developing recommendations for conducting a qualitative financial analysis of an environmental enterprise. To achieve the set goals and objectives, the following methods were applied: of formalization, observation, statistical and dynamic comparative analysis, and economic experiment. The result of such a study was the determination of the features of the financial analysis of an enterprise in a particular industry (using the example of the environmental company LLC «LEMVA»). As a result of the analysis of the factors influencing the assessment of the activities of an environmental enterprise, the features of such an analysis are determined, the directions that should be paid special attention to when conducting it are highlighted.